BARIATRIC SURGERY FOR MORBID OBESITY TREATMENT - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
KUBANG KERIAN, July 2015 A person is classified as being affected by severe or morbid obesity if he or she has a Body Mass Index (BMI) of 35 to 40 or more and experiencing obesityrelated health conditions such as high blood pressure and diabetes.